2020
DOI: 10.1167/tvst.9.13.26
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Visual Field With Peripapillary Vessel Density Through Optical Coherence Tomography Angiography in Normal-Tension Glaucoma

Abstract: Purpose To investigate the retinal vessel density (VD) in healthy and normal-tension glaucoma (NTG) eyes through optical coherence tomography angiography (OCTA) and to determine the correlation between VD and the retinal nerve fiber layer (RNFL) thickness and functional visual field (VF) defects for different locations. Methods A total of 74 NTG eyes and 24 healthy eyes were included. OCTA VD at 4.5 × 4.5 mm peripapillary region and 3.0 × 3.0 mm macula area, RNFL thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
1
9
2
1
Order By: Relevance
“…We found similar vascular-anatomic change patterns present in glaucomatous eyes as seen in other studies on OCTA, corroborating data showing that ST and IT areas of the ONH are more vulnerable to nerve damage in patients with glaucoma [ 11 14 ]. Of note, some other studies have shown higher correlational values across sectors than what we demonstrated; however, most of these studies were analyzing one or two types of glaucoma and were mostly composed of homogeneous populations [ 7 , 12 , 21 ]. Future studies aimed at inspecting the utility of OCTA with more diverse populations should be implemented to validate a more universal utility for OCTA imaging in glaucoma.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…We found similar vascular-anatomic change patterns present in glaucomatous eyes as seen in other studies on OCTA, corroborating data showing that ST and IT areas of the ONH are more vulnerable to nerve damage in patients with glaucoma [ 11 14 ]. Of note, some other studies have shown higher correlational values across sectors than what we demonstrated; however, most of these studies were analyzing one or two types of glaucoma and were mostly composed of homogeneous populations [ 7 , 12 , 21 ]. Future studies aimed at inspecting the utility of OCTA with more diverse populations should be implemented to validate a more universal utility for OCTA imaging in glaucoma.…”
Section: Discussioncontrasting
confidence: 52%
“…These results show that the superotemporal, superonasal, and inferotemporal sector changes of the ONH have the highest correlation with visual field pattern deviation changes [ 11 14 ]. However, many studies designed to evaluate OCTA only include subjects with primary open angle glaucoma (POAG) and normal tension glaucoma (NTG) [ 5 7 , 10 12 , 14 , 15 ]. Furthermore, some of these previous studies only measured differences between the people of European and African descent [ 5 7 , 15 ] or studied a racially or ethnically homogeneous population [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[89][90][91] Another recent study using OCT-A also demonstrated vessel density (VD) reduction in the peripapillary retina and superficial macula area in NTG eyes. 92 The microvascular dropout of VD in the peripapillary retina, especially in the inferotemporal sector, provided a more accurate anatomic correlation with functional VF defects than that of the RNFL thickness, especially in early-stage NTG eyes. 92 On the other hand, data in vascular geometry in NTG, are lacking.…”
Section: Factors In Addition To Iop: Vascular Geometry: Fractalsmentioning
confidence: 95%
“…92 The microvascular dropout of VD in the peripapillary retina, especially in the inferotemporal sector, provided a more accurate anatomic correlation with functional VF defects than that of the RNFL thickness, especially in early-stage NTG eyes. 92 On the other hand, data in vascular geometry in NTG, are lacking. Our group therefore sets out to investigate, using OCT-A, the correlation between cpVD, circumpapillary fractal dimension (cpFD), and severity of NTG.…”
Section: Factors In Addition To Iop: Vascular Geometry: Fractalsmentioning
confidence: 95%
See 1 more Smart Citation